lean2/library/data/list/basic.lean
2015-01-07 13:38:11 -08:00

280 lines
9.8 KiB
Text
Raw Blame History

This file contains ambiguous Unicode characters

This file contains Unicode characters that might be confused with other characters. If you think that this is intentional, you can safely ignore this warning. Use the Escape button to reveal them.

/-
Copyright (c) 2014 Parikshit Khanna. All rights reserved.
Released under Apache 2.0 license as described in the file LICENSE.
Module: data.list.basic
Authors: Parikshit Khanna, Jeremy Avigad, Leonardo de Moura
Basic properties of lists.
-/
import logic tools.helper_tactics data.nat.basic
open eq.ops helper_tactics nat
inductive list (T : Type) : Type :=
nil {} : list T,
cons : T → list T → list T
namespace list
notation h :: t := cons h t
notation `[` l:(foldr `,` (h t, cons h t) nil) `]` := l
variable {T : Type}
/- append -/
definition append : list T → list T → list T,
append nil l := l,
append (h :: s) t := h :: (append s t)
notation l₁ ++ l₂ := append l₁ l₂
theorem append_nil_left (t : list T) : nil ++ t = t
theorem append_cons (x : T) (s t : list T) : (x::s) ++ t = x::(s ++ t)
theorem append_nil_right : ∀ (t : list T), t ++ nil = t,
append_nil_right nil := rfl,
append_nil_right (a :: l) := calc
(a :: l) ++ nil = a :: (l ++ nil) : rfl
... = a :: l : append_nil_right l
theorem append.assoc : ∀ (s t u : list T), s ++ t ++ u = s ++ (t ++ u),
append.assoc nil t u := rfl,
append.assoc (a :: l) t u := calc
(a :: l) ++ t ++ u = a :: (l ++ t ++ u) : rfl
... = a :: (l ++ (t ++ u)) : append.assoc l t u
... = (a :: l) ++ (t ++ u) : rfl
/- length -/
definition length : list T → nat,
length nil := 0,
length (a :: l) := length l + 1
theorem length_nil : length (@nil T) = 0
theorem length_cons (x : T) (t : list T) : length (x::t) = length t + 1
theorem length_append : ∀ (s t : list T), length (s ++ t) = length s + length t,
length_append nil t := calc
length (nil ++ t) = length t : rfl
... = length nil + length t : zero_add,
length_append (a :: s) t := calc
length (a :: s ++ t) = length (s ++ t) + 1 : rfl
... = length s + length t + 1 : length_append s t
... = (length s + 1) + length t : add.succ_left
... = length (a :: s) + length t : rfl
-- add_rewrite length_nil length_cons
/- concat -/
definition concat : Π (x : T), list T → list T,
concat a nil := [a],
concat a (b :: l) := b :: concat a l
theorem concat_nil (x : T) : concat x nil = [x]
theorem concat_cons (x y : T) (l : list T) : concat x (y::l) = y::(concat x l)
theorem concat_eq_append (a : T) : ∀ (l : list T), concat a l = l ++ [a],
concat_eq_append nil := rfl,
concat_eq_append (b :: l) := calc
concat a (b :: l) = b :: (concat a l) : rfl
... = b :: (l ++ [a]) : concat_eq_append l
... = (b :: l) ++ [a] : rfl
-- add_rewrite append_nil append_cons
/- reverse -/
definition reverse : list T → list T,
reverse nil := nil,
reverse (a :: l) := concat a (reverse l)
theorem reverse_nil : reverse (@nil T) = nil
theorem reverse_cons (x : T) (l : list T) : reverse (x::l) = concat x (reverse l)
theorem reverse_singleton (x : T) : reverse [x] = [x]
theorem reverse_append : ∀ (s t : list T), reverse (s ++ t) = (reverse t) ++ (reverse s),
reverse_append nil t2 := calc
reverse (nil ++ t2) = reverse t2 : rfl
... = (reverse t2) ++ nil : (append_nil_right (reverse t2))⁻¹
... = (reverse t2) ++ (reverse nil) : {reverse_nil⁻¹},
reverse_append (a2 :: s2) t2 := calc
reverse ((a2 :: s2) ++ t2) = concat a2 (reverse (s2 ++ t2)) : rfl
... = concat a2 (reverse t2 ++ reverse s2) : {reverse_append s2 t2}
... = (reverse t2 ++ reverse s2) ++ [a2] : concat_eq_append
... = reverse t2 ++ (reverse s2 ++ [a2]) : append.assoc
... = reverse t2 ++ concat a2 (reverse s2) : {concat_eq_append a2 (reverse s2)⁻¹}
... = reverse t2 ++ reverse (a2 :: s2) : rfl
theorem reverse_reverse : ∀ (l : list T), reverse (reverse l) = l,
reverse_reverse nil := rfl,
reverse_reverse (a :: l) := calc
reverse (reverse (a :: l)) = reverse (concat a (reverse l)) : rfl
... = reverse (reverse l ++ [a]) : concat_eq_append
... = reverse [a] ++ reverse (reverse l) : reverse_append
... = reverse [a] ++ l : reverse_reverse
... = a :: l : rfl
theorem concat_eq_reverse_cons (x : T) (l : list T) : concat x l = reverse (x :: reverse l) :=
calc
concat x l = concat x (reverse (reverse l)) : {(reverse_reverse l)⁻¹}
... = reverse (x :: reverse l) : rfl
/- head and tail -/
definition head [h : inhabited T] : list T → T,
head nil := arbitrary T,
head (a :: l) := a
theorem head_cons [h : inhabited T] (a : T) (l : list T) : head (a::l) = a
theorem head_concat [h : inhabited T] {s : list T} (t : list T) : s ≠ nil → head (s ++ t) = head s :=
cases_on s
(take H : nil ≠ nil, absurd rfl H)
(take x s, take H : x::s ≠ nil,
calc
head (x::s ++ t) = head (x::(s ++ t)) : {!append_cons}
... = x : !head_cons
... = head (x::s) : !head_cons⁻¹)
definition tail : list T → list T,
tail nil := nil,
tail (a :: l) := l
theorem tail_nil : tail (@nil T) = nil
theorem tail_cons (a : T) (l : list T) : tail (a::l) = l
theorem cons_head_tail [h : inhabited T] {l : list T} : l ≠ nil → (head l)::(tail l) = l :=
cases_on l
(assume H : nil ≠ nil, absurd rfl H)
(take x l, assume H : x::l ≠ nil, rfl)
/- list membership -/
definition mem : T → list T → Prop,
mem a nil := false,
mem a (b :: l) := a = b mem a l
notation e ∈ s := mem e s
theorem mem_nil (x : T) : x ∈ nil ↔ false :=
iff.rfl
theorem mem_cons (x y : T) (l : list T) : x ∈ y::l ↔ (x = y x ∈ l) :=
iff.rfl
theorem mem_concat_imp_or {x : T} {s t : list T} : x ∈ s ++ t → x ∈ s x ∈ t :=
induction_on s or.inr
(take y s,
assume IH : x ∈ s ++ t → x ∈ s x ∈ t,
assume H1 : x ∈ y::s ++ t,
have H2 : x = y x ∈ s ++ t, from H1,
have H3 : x = y x ∈ s x ∈ t, from or_of_or_of_imp_right H2 IH,
iff.elim_right or.assoc H3)
theorem mem_or_imp_concat {x : T} {s t : list T} : x ∈ s x ∈ t → x ∈ s ++ t :=
induction_on s
(take H, or.elim H false.elim (assume H, H))
(take y s,
assume IH : x ∈ s x ∈ t → x ∈ s ++ t,
assume H : x ∈ y::s x ∈ t,
or.elim H
(assume H1,
or.elim H1
(take H2 : x = y, or.inl H2)
(take H2 : x ∈ s, or.inr (IH (or.inl H2))))
(assume H1 : x ∈ t, or.inr (IH (or.inr H1))))
theorem mem_concat (x : T) (s t : list T) : x ∈ s ++ t ↔ x ∈ s x ∈ t :=
iff.intro mem_concat_imp_or mem_or_imp_concat
theorem mem_split {x : T} {l : list T} : x ∈ l → ∃s t : list T, l = s ++ (x::t) :=
induction_on l
(take H : x ∈ nil, false.elim (iff.elim_left !mem_nil H))
(take y l,
assume IH : x ∈ l → ∃s t : list T, l = s ++ (x::t),
assume H : x ∈ y::l,
or.elim H
(assume H1 : x = y,
exists.intro nil (!exists.intro (H1 ▸ rfl)))
(assume H1 : x ∈ l,
obtain s (H2 : ∃t : list T, l = s ++ (x::t)), from IH H1,
obtain t (H3 : l = s ++ (x::t)), from H2,
have H4 : y :: l = (y::s) ++ (x::t),
from H3 ▸ rfl,
!exists.intro (!exists.intro H4)))
definition mem.is_decidable [instance] (H : decidable_eq T) (x : T) (l : list T) : decidable (x ∈ l) :=
rec_on l
(decidable.inr (not_of_iff_false !mem_nil))
(take (h : T) (l : list T) (iH : decidable (x ∈ l)),
show decidable (x ∈ h::l), from
decidable.rec_on iH
(assume Hp : x ∈ l,
decidable.rec_on (H x h)
(assume Heq : x = h,
decidable.inl (or.inl Heq))
(assume Hne : x ≠ h,
decidable.inl (or.inr Hp)))
(assume Hn : ¬x ∈ l,
decidable.rec_on (H x h)
(assume Heq : x = h,
decidable.inl (or.inl Heq))
(assume Hne : x ≠ h,
have H1 : ¬(x = h x ∈ l), from
assume H2 : x = h x ∈ l, or.elim H2
(assume Heq, absurd Heq Hne)
(assume Hp, absurd Hp Hn),
have H2 : ¬x ∈ h::l, from
iff.elim_right (not_iff_not_of_iff !mem_cons) H1,
decidable.inr H2)))
/- find -/
section
variable [H : decidable_eq T]
include H
definition find : T → list T → nat,
find a nil := 0,
find a (b :: l) := if a = b then 0 else succ (find a l)
theorem find_nil (x : T) : find x nil = 0
theorem find_cons (x y : T) (l : list T) : find x (y::l) = if x = y then 0 else succ (find x l)
theorem find.not_mem {l : list T} {x : T} : ¬x ∈ l → find x l = length l :=
rec_on l
(assume P₁ : ¬x ∈ nil, _)
(take y l,
assume iH : ¬x ∈ l → find x l = length l,
assume P₁ : ¬x ∈ y::l,
have P₂ : ¬(x = y x ∈ l), from iff.elim_right (not_iff_not_of_iff !mem_cons) P₁,
have P₃ : ¬x = y ∧ ¬x ∈ l, from (iff.elim_left not_or_iff_not_and_not P₂),
calc
find x (y::l) = if x = y then 0 else succ (find x l) : !find_cons
... = succ (find x l) : if_neg (and.elim_left P₃)
... = succ (length l) : {iH (and.elim_right P₃)}
... = length (y::l) : !length_cons⁻¹)
end
/- nth element -/
definition nth [h : inhabited T] : list T → nat → T,
nth nil n := arbitrary T,
nth (a :: l) 0 := a,
nth (a :: l) (n+1) := nth l n
theorem nth_zero [h : inhabited T] (a : T) (l : list T) : nth (a :: l) 0 = a
theorem nth_succ [h : inhabited T] (a : T) (l : list T) (n : nat) : nth (a::l) (n+1) = nth l n
end list